2018
DOI: 10.1080/21645515.2018.1459252
|View full text |Cite
|
Sign up to set email alerts
|

Measuring trust in vaccination: A systematic review

Abstract: Vaccine acceptance depends on public trust and confidence in the safety and efficacy of vaccines and immunization, the health system, healthcare professionals and the wider vaccine research community. This systematic review analyses the current breadth and depth of vaccine research literature that explicitly refers to the concept of trust within their stated aims or research questions. After duplicates were removed, 19,643 articles were screened by title and abstract. Of these 2,779 were screened by full text,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
546
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(602 citation statements)
references
References 73 publications
43
546
2
11
Order By: Relevance
“…Trust in vaccination is not always specifically evaluated. 20 The causes of reduced patient trust and the impact on HCPs have not, to our knowledge, been explored. The negative impact of rapidly changing and complex vaccination schedules on vaccinators has also perhaps been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in vaccination is not always specifically evaluated. 20 The causes of reduced patient trust and the impact on HCPs have not, to our knowledge, been explored. The negative impact of rapidly changing and complex vaccination schedules on vaccinators has also perhaps been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Further, many models fail to measure trust, yet trust in vaccination arises as a relevant phenomenon in both qualitative accounts of under-vaccination and the influence of vaccine safety scares (90). Trust is often "ill-defined and a loosely measured concept" (91). Recent work on the moral foundations of behaviour suggests that measuring constructs such as contamination and liberty are also relevant (92,93).…”
Section: Discussionmentioning
confidence: 99%
“…The term 'trust' has an array of meanings in the medical literature. To put it simply in the context of vaccine and vaccination, it is about making a risk versus benefit decision when someone has incomplete or inadequate information 66 . A few studies have shown that VH is closely related to the idea of trust in health professionals and health providers, including the health system and health institutions 67,68 .…”
Section: Determinants Of Vhmentioning
confidence: 99%
“…Benin et al 20 noticed that trust, or the lack of it, forms the basis for parents to either vaccinate or not vaccinate their children, while Larson et al have pointed out that trust placed in the healthcare system, in the healthcare workers, and also in the policy makers who decide on the vaccination programs, mediates the impact of these factors on vaccine hesitancy 17 . It is also interesting to note that the level of trust in the healthcare system is much lower among religious and ethnic minorities 66 . Perhaps this distrust could be traced back to way these minority groups were either neglected or discriminated against by the government that provides the healthcare system 66 .…”
Section: Determinants Of Vhmentioning
confidence: 99%
See 1 more Smart Citation